Energy-exergy-economic-environmental-energo-exergo-enviroecono (7E) analysis of solar photovoltaic power plant: a case study of 7 airport sites in India - S., Sreenath; K., Sudhakar; A. F., Yusop (Elsevier, 2021)
Solar PV development gained airport operators' attention in the wake of its negligible carbon emission and onsite electricity generation. The solar PV projects in airports cater to its energy, economic and environmental needs. A comprehensive study on multi-dimensional performance aspects of the airport-based solar PV system is not presented anywhere. This study investigates the energy, exergy, economic, environmental, energoeconomic, exergoeconomic, and enviroeconomic (7E) performance of solar PV power plant proposed in the premises of 7 Indian airports. For the ease of performance comparison, an identical 5Â MW solar PV system is designed for each airport location. At first, the energy generation, economic, and environmental performance are assessed with the help of RETScreen software. Then, an Excel-based mathematical model was developed to estimate exergy, energoeconomic, exergoeconomic, and enviroeconomic parameters. Satisfactory performance ratio (more than 79) and system efficiency (more than 14) are predicted in all the selected airport locations. The minimum and maximum values of exergy efficiency are estimated as 9.89 (Goa airport) and 12.00 (Lucknow airport), respectively. Except for Ahmedabad airport and Dehradun airport, the IRR value is less than the discount rate (10) for the five airports, with Goa airport on the borderline (9.5). Dehradun airport has the most favorable 7E parameters among the selected seven airports with 82.21 PR, 20.56 CUF, 15.13 exergy efficiency, 3.7Â years payback, 13.30 IRR, 7.5 cents LCOE, 8060 tCO2 avoided/ annum. In addition, it has the lowest value of exergoeconomic & energoeconomic parameter and the highest value of enviroeconomic performance among the selected locations. The application of the 7E framework is expected to provide valuable insights into the feasibility study of the solar photovoltaic system in airports.